Smoking and long-term labour market outcomes - Petri Böckerman; Ari Hyytinen; Jaakko Kaprio (BMJ PUBLISHING GROUP, 2022)
Conclusions Smoking is negatively related to long-term labour market outcomes. The provision of information about the indirect monetary costs of smoking may thus complement the policy efforts that aim at educating consumers about the health costs of smoking.